PERANCANGAN MEDIA PROMOSI BAND BIG BROADSIDE DALAM BENTUK VIDEO KLIP - MUHAMMAD FACHRUROZI, Dra. Zubaidah, M. Sn, San Ahdi, S.Sn., M.Ds (DEKAVE : Jurnal Desain Komunikasi Visual, 2015)
Advertising media and supporting media like video clip are really needed in to a successful indie group bands as BIG BROADSIDE, that promotes song of them to the community so that they can be major label band, and be able to enter the world a recording. Hence, designers a creative must be sensitive to on changes in trend in effect in society and have to find a new innovation. The development of the digital world make the community become get used to things modern and there must be learned the gaps.Design media promotion video clip band BIG BROADSIDE a that they used analysis training. Strenght from media promotion band that will be designed, Weakness of a promotion previous band , Opportunity as seen from the data own observations, and Treath. found of the data own observations. Its consideration is because analysis training especially be used to assess and assess repeated (reevaluasi) a things have been exist and have been previously decided for the purpose to minimize risk that might arise.Kata kunci :Klip video, band,